Analysis of Using Break Even Point and Margin of Safety Information as a Basis for Determining Production Quantity in Controlling Sales Risks at Sumedang Tofu Amira Factory - Amaliza Khaira; Yenni Samri Juliati Nasution; Muhammad Lathief Ilhamy Nasution (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the utilization of Break Even Point (BEP) and Margin of Safety (MOS) information as a basis for determining production quantities in controlling sales risk at Amira Sumedang Tofu Factory. The study is motivated by fluctuating market demand and the perishable nature of tofu products, which require effective production planning to minimize the risk of financial losses. A descriptive quantitative approach was employed using primary and secondary data collected through observations, interviews, documentation, and business records. The analysis was conducted using Cost-Volume-Profit (CVP) techniques, particularly Break Even Point (BEP) and Margin of Safety (MOS) calculations. The findings indicate that the factory’s sales consistently remained above the break-even point during the January–April 2026 period, demonstrating the company’s ability to cover all production costs and generate profits. The calculated BEP sales value was IDR 14,950,166, while actual monthly sales ranged from IDR 35,750,000 to IDR 42,240,000. Furthermore, the Margin of Safety values ranged from 58.2% to 64.6%, indicating that the company maintained a strong sales safety margin and faced a relatively low risk of financial loss. The highest MOS value was recorded in January (64.6%), while the lowest occurred in February (58.2%), although sales remained safely above the break-even level. The study concludes that BEP and MOS are effective management accounting tools for supporting production planning and controlling sales risk. BEP provides information regarding the minimum sales and production levels required to avoid losses, while MOS measures the degree of sales security against potential declines in demand. Therefore, the utilization of BEP and MOS information can assist MSMEs in making more accurate production decisions, improving operational efficiency, and maintaining business sustainability in a competitive market environment.